Effectiveness of Different Storage Conditions and Sanitizers of the Post Harvest Performance of Sweet Pepper (Capsicum annum L.) in Chitwan District, Nepal - Kalauni, Santosh; Tripathi, Kalyani Mishra; Shrestha, Arjun Kumar; Shrestha, Bishal (Nepalese Horticulture, 2020)
To investigate the effectiveness of different Storage conditions and Sanitizer treatments on the postharvest performance of the fruits of Sweet pepper var. California Wonder, an experiment was laid out in two factorial Randomized Complete Block Design (RCBD) with three replications. Fruits subjected to Sanitizer treatments viz Sodium hypochlorite @ 0.02%, Calcinated calcium @ 0.1%, Neem extract @10%, Aloe vera @10% and Control were stored under Evaporative Cooling (EC) and Ambient conditions. Observations were recorded for Physiological loss in weight (PLW), Total soluble solid (TSS), Titratable acidity (TA), Vitamin C, Spoilage percentage and Shelf life of the fruits. At the end of the shelf life, the main effects of Storage conditions and Sanitizers were found significant for PLW, Spoilage percentage, TSS, Vitamin C and Shelf life. The lowest PLW (13.19%) was observed in the fruits stored in EC condition compared to the fruits kept in Ambient storage (21.61%). EC storage showed the lowest Spoilage percentage (41.1%), the longest Shelf life (13.8 days), the highest TSS (3.16°Brix) and Vitamin C (53.7 mg/100g). Among the Sanitizers, the lowest PLW (14.69%) and Spoilage percentage (37.5%) were recorded in the treatment of Sodium hypochlorite followed by Aloe vera solution. Likewise, the highest TSS (3.63°Brix), Vitamin C (52.8 mg/100 g) and the longest Shelf life (13.33 days) were recorded under the treatment of Aloe vera solution. The treatment combination of EC storage and Sodium hypochlorite exhibited the lowest PLW on 9th day (11.05%) of storage. The results suggest that the postharvest quality and shelf life of sweet pepper can be extended by storing the sweet pepper fruits in energy efficient EC storage after the application of Sanitizers viz. Sodium hypochlorite and Aloe vera.